2018
DOI: 10.1289/ehp1965
|View full text |Cite
|
Sign up to set email alerts
|

Community-Led Total Sanitation: A Mixed-Methods Systematic Review of Evidence and Its Quality

Abstract: Background:Community-led total sanitation (CLTS) is a widely applied rural behavior change approach for ending open defecation. However, evidence of its impact is unclear.Objectives:We conducted a systematic review of journal-published and gray literature to a) assess evidence quality, b) summarize CLTS impacts, and c) identify factors affecting implementation and effectiveness.Methods:Eligible studies were systematically screened and selected for analysis from searches of seven databases and 16 websites. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
142
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 53 publications
5
142
1
Order By: Relevance
“…Prior to the intervention, many of the program countries had existing government-supported CLTS activities taking place, and in many cases SNV was involved in those pilots. Countries also had, to some extent, efforts to improve supply-chain [17,18]. However, at the time, CLTS was implemented at the village level and while successful in a number of villages, there was no clear road to scale or sustainability.…”
Section: Pre-study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the intervention, many of the program countries had existing government-supported CLTS activities taking place, and in many cases SNV was involved in those pilots. Countries also had, to some extent, efforts to improve supply-chain [17,18]. However, at the time, CLTS was implemented at the village level and while successful in a number of villages, there was no clear road to scale or sustainability.…”
Section: Pre-study Contextmentioning
confidence: 99%
“…Stalled progress and slippage were important problems that SSH4A hoped to address. Stalled progress occurred in many of these countries for various reasons, including remaining villages are often more rural and difficult to reach with CLTS campaigns, late adopters are often less interested in the interventions, quality of triggering, supply chain limitations, and scaling strategies and both human and monetary resources are sometimes inadequate [18]. Slippage has also been a considerable problem as CLTS interventions often result in unimproved or low durability latrines [19].…”
Section: Pre-study Contextmentioning
confidence: 99%
“…• Unlike Venkataramanan et al (2018) we will focus only on studies that analysed CLTS in rural or semi-rural settings. We believe that sanitation poses quite different challenges in urban settings and that it is not appropriate to synthesise evidence from urban and rural settings together.…”
Section: Why It Is Important To Do the Reviewmentioning
confidence: 99%
“…However, it also means that they extracted factors influencing CLTS from all of the 200 studies of which a large part was assessed as of low quality. We consider their finding about generally poor quality of evidence as a starting point and, unlike Venkataramanan et al (2018), we will use a quality and information content appraisal to select and consider only studies of acceptable quality for the extraction of data on the second review question. Venkataramanan et al (2018) descriptively characterised outcomes and influencing factors identified from the considered primary studies but did not report on links between particular factors and specific outcomes. The latter is one of the main goals of our review with respect to the second review question.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the goal is met by 2015, 5.4 million children will still die. 4 Human faeces left in the open fields, bushes or drains generate millions of viruses, bacteria and parasites. House flies usually fly between these faeces and the food we eat including fruits.…”
Section: Introductionmentioning
confidence: 99%